Is breaking of bad news indeed unacceptable to native Africans? A cross‐sectional survey of patients in a Nigerian neurosurgical service. (19th June 2012) - Adeleye, A. O.; Fatiregun, A. A.
<x xml:space="preserve">Abstract</x> Objectives Breaking of bad news is anecdotally deemed to be culturally unacceptable, even intolerable, to native Africans. We sought whether this hypothesis could be formulated among a cohort of patients who had difficult diagnoses given them in a Nigerian neurosurgical service. Materials and Methods A semi‐structured, interviewer‐administered questionnaire was used in a cross‐sectional survey among a consecutive cohort of patients on their opinion and preferences regarding the full disclosure of the grave prognoses of their difficult neurosurgical diagnoses. Results A total of 109 patients, 74 (67.9%) males, were sampled over a one‐and‐half‐year period. They were mainly young adults, mean age of 40.2 (SD 14.2) years; more than half of them, 56%, had only basic literacy education, but the majority, 99.1%, declared themselves to have serious religious commitments. Less than 3% of the study participants chose not to receive their medical bad news whilst the majority who preferred to have the full disclosure of their medical diagnosis wanted their relations around during the process in 88%, and indeed, 91% would not be happy to be kept in the dark by their knowing relations. Finally, whilst the majority (98%) did not see the prospects of getting any governmental support, hope in God (88%) and family support (40%) were the means by which they expected to cope with the realities of their new futures. Conclusions This data‐driven study showed that contrary to anecdotal belief breaking bad news was not intolerable to a cohort of native Nigerian‐African patients in a neurosurgical practice.